TRANSFORMASI BERBASIS DIGITAL PADA PETANI TANAMAN HIAS CIHIDEUNG PARONGPONG BANDUNG BARAT - Heddry Purba; Francis Hutabarat; Joan Y. Hutapea; Ria Chaniago; Lenita Waty (Bajang Institute, 2026)
This community service activity aims to encourage digital transformation among ornamental plant farmers in Cihideung Village, Parongpong District, West Bandung Regency, who have faced challenges in online marketing and digital literacy. The program is implemented through a partnership between the university, the Cihideung Village Government, and the Ornamental Plant Farmers Cooperative. Implementation methods include administrative coordination, focus group discussions (FGDs) to identify needs, development of the Astuti Flower Parongpong marketplace website, digital marketing training, and integration of a QRIS-based digital payment system. The results of the activity indicate an increase in farmers' ability to use digital platforms, manage product catalogs, and utilize social media for promotion. Quarterly evaluations noted an increase in online transactions and an expansion of market reach beyond the region. Key success factors were collaboration between parties and institutional support, while the main obstacles included limited infrastructure and consistent website management. This program serves as a pilot model for the development of an agriculture-based creative economy in the West Bandung region. Going forward, ongoing collaboration is expected to expand export access and strengthen the digital independence of Cihideung ornamental plant farmers.